Remote Sensing and GIS Aided Land and Water Management Plan Preparation of Watershed - A Case Study - Paul, J C; Mishra, J N; Pradhan, P L; Sharma, S D (Journal of Agricultural Engineering, 2008)
Remote Sensing and GIS techniques were applied for the integrated watershed planning of Bajpur watershed in Khurda sadar block of Khurda district (Orissa). IRS ID, LISS III F.c.c. satellite images and toposheet number 73H/12 together with verification were used as the data source. Thematic maps like land use/ land cover map, hydrogeomorphology map, soil map, slope map, drainage and surface water body maps were prepared by using both satellite imageries and survey of India toposheet. By integrating all these maps in GIS, water and land resource management plans were developed. The water resources development plan indicates the sites for groundwater exploitation and sites for surface water development including sites for different soil and water conservation structures. Eleven action items were suggested under land resource action plan with specific sites, aerial locations and maps. Thus remote sensing technology demonstrates the usefulness for providing up-to-date, reliable and accurate information on different natural resources of the watershed which is a pre-requisite for an integrated approach to identify the suitable sites for water harvesting structures, check dams, farm ponds, percolation tanks, nala bunds etc. The GIS technique is helpful to integrate the information into a composite land unit development map to generate alternate land use system for sustainable development of the watershed.